Reconstructing the Structure of the Qur'an: Al-Ghazali's Sufistic Approach - Lutfi, Achmad (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This article discusses al-Ghazali's thoughts regarding the structure of the Qur'an which is different from generally known patterns. Al-Ghazali with his Sufistic tendencies rearranged the verses and letters of the Koran into two categories, namely Jawahir and Durar. Jawahir is a verse that is directly related to the nature of Allah, while Durar is a verse that contains instructions to Allah's servants to follow the straight path through righteous deeds that are carried out firmly. Al-Ghazali views the Koran as a means to achieve makrifatullah. The research method used is a literature study with a structuralist approach by examining relevant primary and secondary sources. This article shows that Al-Ghazali's structure of the Qur'an is unique and new, namely linking the verses of the Qur'an to the nature of Allah and the straight path to makrifatullah. This article also contributes to the development of Al-Qur'an studies, especially in the fields of structure and Sufism.